Conducting competitive analysis - Levy, Jaime (O'Reilly, 2018)
In this lesson, you'll learn that the competitive analysis helps you gain insight into current trends as to what is or is not working. Knowing the unknowns helps your team to not repeat mistakes but instead make good ideas better. A good analysis also exposes gaps and opportunities for your product to take advantage of in the marketplace.